2020
DOI: 10.4049/jimmunol.2000305
|View full text |Cite|
|
Sign up to set email alerts
|

Zebrafish F-box Protein fbxo3 Negatively Regulates Antiviral Response through Promoting K27-Linked Polyubiquitination of the Transcription Factors irf3 and irf7

Abstract: FBXO3, belongs to the F-box family of proteins, which has been reported to involve in host autoimmune and inflammatory responses by promoting its substrates for ubiquitylation. However, thus far, its physiological function in antiviral immunity remains elusive. In this study, we report that overexpression of zebrafish fbxo3 suppresses cellular antiviral responses. Moreover, disruption of fbxo3 in zebrafish increases the survival rate upon spring viremia of carp virus exposure. Further assays indicate that fbxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…*p < 0.05. induce IFN during viral infections, IRF3 overexpression is sufficient to induce IFN without viral infection in fish because IRF3 is an IFN-inducible protein that can be activated by IFN (23). Therefore, IRF3 degradation by regulatory factors to avoid excessive activation is necessary in fish (31). In the current study, our data demonstrated that Uba1 promotes the degradation of IRF3.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…*p < 0.05. induce IFN during viral infections, IRF3 overexpression is sufficient to induce IFN without viral infection in fish because IRF3 is an IFN-inducible protein that can be activated by IFN (23). Therefore, IRF3 degradation by regulatory factors to avoid excessive activation is necessary in fish (31). In the current study, our data demonstrated that Uba1 promotes the degradation of IRF3.…”
Section: Discussionsupporting
confidence: 52%
“…Zebrafish Forkhead box O (FOXO) 3b represses the IFN response by impeding the transcriptional activity of IRF3 (30). Another Fbox protein family member, fbxo3, promotes K27-linked polyubiquitination and the degradation of IRF3 (31). In general, the mechanisms that contribute to the termination of IRF3-IFN signaling in fish are still unclear.…”
mentioning
confidence: 99%
“…Although the endosomal recruitments of Sec61 and p97 play vital roles in cross‐presentation, 24,29 the recycling of MHC class I molecules was also documented to increase cross‐presentation via UCH‐L1‐mediated ubiquitination 7 . At the same time, K27‐linked ubiquitination was verified to promote proteasomal degradation of irf3 and irf7 30 and inhibit UCHL3 degradation 31 . In the present study, although K27 and K48‐linked ubiquitination regulates cross‐presentation, the exact roles of the endosomal recruitments of p97/Sec61 and the recycling of MHC class I molecules in K27 or K48‐linked ubiquitination regulating cross‐presentation still need further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TRIM21 and PSMD14 cooperatively regulate the K27‐linked ubiquitination of IRF3 to ensure appropriate activation of type I IFN signaling. In zebrafish, E3 ligase fbxo3 induces K27‐linked ubiquitination of IRF3 and IRF7, leading to proteasomal degradation to suppress antiviral responses 79 . As the FBXO3 gene is evolutionary conserved, the biologic function of FBXO3 may show a similar effect on human beings.…”
Section: K27‐linked Ubiquitination In Innate Immunitymentioning
confidence: 99%